En lärdom för livet? : Internationellt samarbete i skolan - Hinnemo, Venla (2011)
The aim of this study was to explore what pupils in an upper secondary school inLuleå in northern Sweden learned from participating in an international exchangeproject and how their cultural inheritance can be utilized in their daily education. Byconducting qualitative interviews with pupils and teachers of the Luleå uppersecondary school, the following topics were discussed: knowledge and experience,roots and roles in educational situations.The results showed that interest, excitement and a will to help others are elements thatconnect the interviewed pupils with the project. Both pupils and teachers find thatexchange programs are functional methods for increasing understanding in diversesurroundings through various dimensions. The pupils believe that their culturalinheritances are important, although each pupil’s relation with her own culturalinheritance varies. Within the exchange project you find informal learning through theacquisition of knowledge outside the boundaries of school. The socio cultural learningexists between and within the participating groups and intercultural learning appearse.g. through deeper knowledge of other peoples’ customs and ways of living.The author thinks that methods within intercultural education are subjects for furtherresearch, in purpose of teachers, teacher students and pupils obtaining a strongerconnection to these methods. Validerat; 20110223 (anonymous)